Composition in Iranian Painting with Emphasis on the Theme and Principles of Visual Traditions - ehsan zarei farsani; maryam ghasemi (Jilvah-i hunar, 2019)
The concern of accurately representing the elements of the world around, in a work of art under the technical skill of the artist, sometimes repels the interaction between these elements for the sake of desirable generality. Consequently, relying on the strict representation of the elements of the scene and the lack of attention to design principles in the work will not be sufficient to achieve the target audience. The artist uses the necessary visual arrangements to make sense of the scene in the body and soul of the viewer and to convey the sense of content through the necessary measures. Departure of Iranian paintings from walls to manuscript forms a profound link between Persian literature and Iranian art. The Mongol conquest of Iran was a turning point in the history of the painting of this land. Another process of adaptations and innovations began in the late 13th century AD. With the introduction of bibliography at the courts, there was a restriction on the social function of painting, but instead, the themes and artistic expression became wider'. The Iranian painter has exhibited some of the most prominent works of literature of this region in the form of design and color, and has contributed his wishes, ambition and imagination. Visual representation of artistic discipline and artistic arrangements in Iranian painting, especially in the schools of Herat and Tabriz, represent the Iranian artist's awareness of the principles of design and the visual study of the valuable works of Iranian painting art is a visible evidence of the application of design principles in this field. The artist achieves visual unity by utilizing visual qualities, artistic tactics, and the principles and rules required in the process of creating a work. The principles of image organizing, harmony, diversity, balance, proportion, mastery, movement and the ability to form a single whole are the guides of the artist. Iranian and Indian-Islamic sources have mainly benefited from the term framework rather than the contemporary term of composition. For example, Mirza Muhammad Haidar Dughlatin the discussion of Behzad -1450-1535 AD wrote as follows: “His pen is tighter and his framework is better than his”. In the works of Tabriz I school, the harmony between image and text, caused horizontal and vertical combinations of events. Symmetrical and sometimes diagonal structures are also visible in these paintings. In some of these works, the artist uses clever tactics to create such a link between the existing elements, the composition and the narrative that the keen eye, after understanding and receiving it, rejoices and camouflaging these measures and applying hidden geometry, doubles the enjoyment of the work. The purpose of this study was to combine composition in Iranian painting with emphasis on the content and principles of visual traditions in a descriptive-analytical method. The present study seeks to draw on the legacy of the fine art of Iranian painting, through extensive research in the form of books and articles, and the author's collection and analysis of the aforementioned cases, conventional, institutional, and authentic tricks and arrangements from the perspective of creating a sense of theme in Iranian painting. In the field of visual traditions, the necessary books and articles are sufficiently accessible, and the conformity of the visual values of Iranian painting with these principles has been the way to achieve the purpose of the present study. Therefore, the results show that Iranian art has long been trying to express deep spiritual thoughts and has been seeking the truth by crossing the boundaries of time and place as elements of perception of reality. The Western artist used all the formal arrangements and techniques of landscapes to create spirituality from the visual elements. The Iranian-Islamic artist, however, tried to immaterialize the world of work. The viewer's feeling against a stimulus will itself be a criterion for measuring the success of a project. The basis of design theory is to discover the conditions under which the viewer's sensory reactions are quite receptive and positive. Design theory is based on the assumption that human sense inherently searches for a particular order within visual stimuli. The result is that the Iranian painter is aware of the principles of visual discipline and does not purport to convey a mere depiction of the elements of the scene in order to convey a sense of variety of themes. Choosing the right frame, the right geometry, and the right composition, along with applying visual qualities and artistic arrangements have been guidance of emotionally believing text and image adaptation. Each theme requires its own structure, composition and geometry, and contemporary themes have often used common tricks and tactics.